New approaches to the plant bioactive compound extraction, isolation, quantification, and characterization (International Journal of Food and Nutritional Sciences, 2022)
Introduction:The molecular diversity observed in natural products derived from medicinal plants, including both pure molecules and standardized extracts, offers vast potential for the discovery of novel therapeutic leads.Methodology: An growing variety of procedures that combine chromatographic and spectroscopic or spectrometric techniques have been devised to elucidate the structures of both known and novel substances, obviating the necessity for separation. While the isolation of pure compounds from complex matrices such as organic matter continues to pose challenges, the development of more selective methods for extraction, fractionation, and purification holds promise for reducing the time required from the collection of biological materials to obtaining the final purified compound. However, it is important to note that the achievement of one-step isolation procedures is still a distant goal. In addition to the various procedures conducted on the plant, a significant deficiency exists in the isolation, identification, and quantification of plant extracts exhibiting notable antioxidant properties.Results: Mass spectrometry is a very effective analytical methodology utilized for the purpose of identifying new compounds, quantifying known substances, and elucidating molecular structure and chemical characteristics. The utilization of an MS spectrum can facilitate the determination of a substance's molecular weight. This method is frequently employed in the field of organic compound structural elucidation, peptide or oligonucleotide sequencing, and monitoring the presence of known compounds in complex mixtures with a high level of specificity. It involves simultaneous determination of the molecular weight and identification of a diagnostic fragment of the molecule